Juridical Review of The Position of The Minister of SOE’s as Beneficial Owner In State Owned Enterprises Group - Husein, Muhammad Syaban (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Beneficial Owner is currently the main focus in discussions regarding Good Corporate Governance ("GCG") in a corporation, including SOE as a corporation owned by the state and managed by the government which is an important subject in the application of the Beneficial Owner context. Therefore, the aim of this research is to analyze the concept of Beneficial Ownership in Indonesia and examine the position of the Minister of SOE as the Beneficial Owner of the SOE Groups (SOE, SOE Subsidiaries and SOE Affiliated Companies). This writing uses normative juridical methods by conducting a literature review. The research results show that in Indonesia the implementation of Beneficial Owners has been regulated through Presidential Decree 13/2018 which has provided definitions and characteristics regarding Beneficial Owners, and in supporting the existence of Presidential Decree 13/2018, several regulations have also been issued, namely Permenkumham No. 15/2019 and Permenkumham 21/2019, each of which regulates procedures for implementation and supervision of Beneficial Owners for SOE Groups. The position of the Minister of SOE as Beneficial Owner is divided into 3 types, namely in BUMN and BUMN Subsidiaries the position of the Minister of BUMN as Beneficial Owner, while SOE affiliated companies, the position of the Minister of SOE can be the Beneficial Owner or not.